VD_FINDINFO Jug / 2014 / 289 vom 12. September 2014 - VD Tribunal cantonal (2014)
JUGE UNIQUE, VIOLATION DES RÈGLES DE LA CIRCULATION, PRIORITÉCIRCULATION | 31 al. 1 LCR, 32 al. 1 LCR, 90 ch. 1 LCR, 398 al. 4 CPP (CH)